2010
DOI: 10.1111/j.1365-2958.2010.07271.x
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin tolerance in clinical and laboratory Streptococcus pneumoniae isolates depends on reduced enzyme activity of the major LytA autolysin or cooperation between CiaH histidine kinase and capsular polysaccharide

Abstract: SummaryVancomycin is frequently added to standard therapy for pneumococcal meningitis. Although vancomycinresistant Streptococcus pneumoniae strains have not been isolated, reports on the emergence of vancomycin-tolerant pneumococci are a cause of concern. To date, the molecular basis of vancomycin tolerance in S. pneumoniae is essentially unknown. We examined two vancomycin-tolerant clinical isolates, i.e. a purported autolysin negative (LytA -), serotype 23F isolate (strain S3) and the serotype 14 strain 'Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…However, in 2010 the first mutation in a ciaH gene of a clinical S. pneumoniae isolate, the vancomycin-tolerant strain Tupelo, was described (Moscoso et al, 2010). The mutated ciaH gene in this strain has been implicated in the vancomycin-tolerance phenotype (Moscoso et al, 2010), which would be consistent with the established role of CiaRH in lysis protection (Dagkessamanskaia et al, 2004;Mascher et al, 2006). Thus, altered ciaH genes do also occur in clinical isolates of S. pneumoniae.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, in 2010 the first mutation in a ciaH gene of a clinical S. pneumoniae isolate, the vancomycin-tolerant strain Tupelo, was described (Moscoso et al, 2010). The mutated ciaH gene in this strain has been implicated in the vancomycin-tolerance phenotype (Moscoso et al, 2010), which would be consistent with the established role of CiaRH in lysis protection (Dagkessamanskaia et al, 2004;Mascher et al, 2006). Thus, altered ciaH genes do also occur in clinical isolates of S. pneumoniae.…”
Section: Introductionmentioning
confidence: 68%
“…Increasing CiaR regulon expression further resulted in the accentuation of the block of competence and elevated b-lactam resistance phenotypes. Since these phenotypes appear to be linked, we wondered if prevention of competence and the concomitant effect on autolysis (Mascher, 2006;Moscoso et al, 2010) would also cause b-lactam resistance. Inactivating either comAB or comDE, the genes involved in early steps of competence induction, had virtually no effect on the growth of these mutants on b-lactam-containing agar plates (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the fitness of antibiotic-resistant bacteria indicated that when the numbers of resistant cells increase above a threshold level, they are likely to remain there for a long time (5). In addition, the pneumococcus is naturally transformable with exogenous DNA, and horizontal DNA transfer among closely related streptococci is evident from the mosaic structure of certain virulence factors, such as the choline-and penicillin-binding proteins (106). Thus, the therapy of pneumococcal diseases is hampered by the increasing prevalence of antibiotic-resistant strains and the suboptimal clinical efficacy of the available vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of spontaneous mutations in TCS have been described in many bacteria that affect various phenotypic characteristics. For example, mutations in TCS have been shown to confer antibiotic resistance in certain strains of Streptococcus pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa, and Enterococcus faecium (53)(54)(55)(56). Clinical isolates containing mutations in the TCS CovR/S (also known as CsrR/S) have been reported in GBS and group A streptococci (GAS) (57,58).…”
Section: Discussionmentioning
confidence: 99%